Optimalisasi “Pondok Paru Sehat” Kelurahan Dukuh Kupang Kota Surabaya Melalui Edukasi Peran Gizi Dalam Penyakit Paru Obstruktif Kronis (PPOK) Dan Pemeriksaan Fungsi Paru (Spirometry) Untuk Deteksi Dini PPOK - Anggraini Soetedjo, Farida; Arimbi, Muzaijadah Retno; Khamidah, Nur; Kristijanto, Johanes Aprilius Falerio (Publikasi Indonesia, 2025)
Chronic Obstructive Pulmonary Disease (COPD) is a leading cause of morbidity and mortality from non-communicable diseases in Indonesia, particularly in Surabaya. The “Pondok Paru Sehat” community service program, initiated by the Faculty of Medicine, Wijaya Kusuma University Surabaya (FK UWKS), aims to raise awareness, knowledge, and early detection of COPD through nutrition education and spirometry screening in Dukuh Kupang sub-district. This study employed a descriptive qualitative approach using the Five Levels of Prevention model, involving 40 participants from both productive age groups and the elderly. The results indicated that 28 participants had an FEV1/FVC ratio of <70%, suggesting undiagnosed airway obstruction. Nutritional status assessment using Body Mass Index (BMI) showed that 30% of participants were underweight, while 20% were overweight. Participant satisfaction reached 92.5%, with the majority considering the education and screening services highly beneficial. The program demonstrates that community-based education combined with lung function screening can enhance awareness and early detection of COPD. This model is recommended for replication in other regions with support from local health cadres, health authorities, and educational institutions.